Relationship between Employee Pre-Retirement Adjustment Styles and Knowledge Sharing Intentions in State Corporation in Kenya. - kembu, Appolonius Shitiabai; Amuhaya, Iravo Mike; Guyo, Wario (IJRDO - Journal of Applied Management Science, 2016)
Knowledge management of the aging workforce is a major challenge, particularly to statecorporations in Kenya. Psychological effects of disengagement from a work life and thetransition to retirement may influence knowledge sharing intensions. The objective of the studywas to examine the relationship between employee pre-retirement Adjustment styles andknowledge sharing intentions in state corporations in Kenya listed in the Kenya Gazette. Thestudy used exploratory design. The population of the study comprised of all 202 StateCorporations in Kenya. The study used purposive sampling to obtain data from the populationthrough a questionnaire. The study targeted employees who were within retirement age.Quantitative data was collected to enable the researcher conduct an in-depth study. The studycarried out a pilot test to test the validity and reliability of the questionnaires in gathering thedata required for purposes of the study. Simple linear regression and multiple regression analyseswas used to establish the nature and magnitude of the relationship between variables and to testhypothesized relationships. The study established that employee pre-retirement adjustment styleshad greater effect on knowledge sharing intentions. The study also established that preretirementanxiety enhanced knowledge sharing intentions in State Corporations in Kenya. Itfurther found that the relationship was stronger where State Corporations were based in the samesector and weaker when they were across Sectors. These research findings contribute by